The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1016/j.bbamem.2014.04.025
|View full text |Cite
|
Sign up to set email alerts
|

A proapoptotic peptide conjugated to penetratin selectively inhibits tumor cell growth

Abstract: The peptide KLA (acetyl-(KLAKLAK)2-NH2), which is rather non toxic for eukaryotic cell lines, becomes active when coupled to the cell penetrating peptide, penetratin (Pen), by a disulfide bridge. Remarkably, the conjugate KLA-Pen is cytotoxic, at low micromolar concentrations, against a panel of seven human tumor cell lines of various tissue origins, including cells resistant to conventional chemotherapy agents but not to normal human cell lines. Live microscopy on cells possessing fluorescent labeled mitochon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(37 citation statements)
references
References 56 publications
0
37
0
Order By: Relevance
“…In such cases, the linker should be cleaved to permit release of the drug conjugated to the CPP. For this purpose, cleavable linkers, such as an acid-labile hydrazone bond [41] or a reductioncleavable disulfide bond [42], have been used. A peptidic bond that can be broken by protease may also be applied [43].…”
Section: Challenges To Cpp Use In Cancer Treatmentmentioning
confidence: 99%
“…In such cases, the linker should be cleaved to permit release of the drug conjugated to the CPP. For this purpose, cleavable linkers, such as an acid-labile hydrazone bond [41] or a reductioncleavable disulfide bond [42], have been used. A peptidic bond that can be broken by protease may also be applied [43].…”
Section: Challenges To Cpp Use In Cancer Treatmentmentioning
confidence: 99%
“…The infant SGF and SIF were prepared as ascribed in the studies of Liu et al, 29 and Dupont et al 30 with slight modification. The pH of SGF and SIF were adjusted to 3.0 and 7.4, respectively.…”
Section: Digestion Of Lf Liposomes Under Simulated Gastric and Small mentioning
confidence: 99%
“…Another study showed that the proapoptotic peptide (KLAKLAK) 2 conjugated to penetratin led to selective inhibition of tumor cell growth. [55] To promote delivery of (KLAKLAK) 2 specifically to the GBM cells, we generated a recombinant protein IL-13-D2-KK2, which targets IL-13RA2. After biotin conjugation and detection with streptavidin, we showed that IL-13-D2-KK2 was effectively internalized into the GBM cells and co-localized with ATP-synthase.…”
Section: Discussionmentioning
confidence: 99%